2014
DOI: 10.1158/0008-5472.can-14-0761
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment-Derived HGF Overcomes Genetically Determined Sensitivity to Anti-MET Drugs

Abstract: Cell-based drug screenings indicate that tumors displaying c-MET gene amplification are "addicted" to MET signaling and therefore are very sensitive to MET-targeted agents. However, these screenings were conducted in the absence of the MET ligand, hepatocyte growth factor (HGF), which is abundant in the tumor microenvironment. Sensitivity of six MET-addicted human tumor cells to three MET kinase inhibitors (JNJ-38877605, PHA-665752, crizotinib) and one antagonistic anti-MET antibody (DN30 Fab) was analyzed in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 43 publications
(52 reference statements)
3
67
0
Order By: Relevance
“…Capmatinib is also predicted to bind to the autoinhibited inactive conformation of MET as a type Ib inhibitor with interactions that involve pi-stacking with Y1230, but independently of G1163. In contrast, glesatinib exhibits a structure like type II inhibitors in the literature (30)(31)(32) and extends linearly toward the aC helix and hydrophobic back DFG-out pocket with a predicted primary binding mode as a type II inhibitor in catalytically inactive state. Glesatinib also appears capable of adopting a secondary binding mode to a DFG-in catalytically active state, extending back into a hydrophobic I1145 pocket between the aC helix and catalytic K1110.…”
Section: Resultsmentioning
confidence: 95%
“…Capmatinib is also predicted to bind to the autoinhibited inactive conformation of MET as a type Ib inhibitor with interactions that involve pi-stacking with Y1230, but independently of G1163. In contrast, glesatinib exhibits a structure like type II inhibitors in the literature (30)(31)(32) and extends linearly toward the aC helix and hydrophobic back DFG-out pocket with a predicted primary binding mode as a type II inhibitor in catalytically inactive state. Glesatinib also appears capable of adopting a secondary binding mode to a DFG-in catalytically active state, extending back into a hydrophobic I1145 pocket between the aC helix and catalytic K1110.…”
Section: Resultsmentioning
confidence: 95%
“…However, transcriptional upregulation has been observed resulting from Stat-3 and c-Src expression [60], and the co-expression of HGF and cMET in tumour cells can drive autocrine activation, as well as increased transcription for both genes. A number of studies have identified that HGF expression and autocrine cMET activation decreases sensitivity to cMET inhibitors, and stromal HGF levels have been linked to clinical responses in patients treated with the anti-HGF agent, ficlatuzumab [61][62][63], demonstrating the importance of the use of biomarkers in predicting clinical responses.…”
Section: Mis-regulation Mechanisms Of Hgf/cmetmentioning
confidence: 99%
“…MET-amplified tumor cells normally exhibit ligand-independent, constitutive MET activation [36]. Thus, in cancers driven by MET amplification/overexpression or activating mutations, MET activation and downstream signaling is unlikely to be fully blocked by drugs solely targeting HGF-MET binding.…”
Section: Mechanism Of Resistance To Met Targeted Therapymentioning
confidence: 99%
“…Thus, in cancers driven by MET amplification/overexpression or activating mutations, MET activation and downstream signaling is unlikely to be fully blocked by drugs solely targeting HGF-MET binding. Furthermore, it was recently shown that microenvironmentderived HGF can overcome sensitivity to anti-MET drugs [36]. Similarly, HGF mAb such as rilotumumab alone may not be able to sufficiently attenuate MET signaling in HGF-independent tumors to deliver clinical benefit.…”
Section: Mechanism Of Resistance To Met Targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation